A. F. Büsching and the Place of Geographical Knowledge in the German Enlightenment, c. 1740 - 1800 - Bond, Dean W. (2016)
This dissertation places geographical knowledge and practice in the German Enlightenment (Aufklärung). I illustrate something of geography's constitutive sites and practical making by discussing the life and work of Anton Friedrich Büsching (1724-93), who made his name as one of the foremost geographers in the German lands and Europe through his Neue Erdbeschreibung (Hamburg, 1754-92), and through his geographical periodicals. I consider Büsching's geographical project and its social, political and scientific contexts in three articles. The first concerns the making of geographical knowledge 'at home' in the context of Büsching's geography of Asia (Hamburg, 1768) and the Royal Danish Expedition to Arabia (1761-67) organised by Johann David Michaelis. I illustrate how Büsching and Michaelis sought to integrate knowledge of the study and the field in ways that allowed them to produce more accurate knowledge of Asia's geography, and to legitimate the credibility of textual critique in the study. I argue that understanding the relations between the constitution of the study as an analytic site and the evaluation of knowledge from the field is crucial for understanding the making of Enlightenment geography. The second article concerns the place of geography in print, and focusses on Büsching's 'learned newspaper', the Wöchentliche Nachrichten (Berlin, 1773-87). I argue his periodical played a central role in reshaping the moral economy of geographical knowledge in the later eighteenth century, and show that the periodicity and materiality of the periodical genre transformed the character of geography’s authors and audiences in the Aufklärung. The final article discusses the place of politics in German geography. I argue that geography was politicised through inscriptive practices of authorship, correspondence and learned journalism, and through practices of mapping and education. Moreover, I contend that that Büsching's geographical project was politicised through his work on the geography of the Holy Roman Empire and through his periodicals, because these works were a means for improving geo-literacy, and for engendering a sense of pride in both 'Germany' as a cultural nation and in Frederick II's Prussia. Collectively, the dissertation demonstrates the centrality of Büsching's geographical project to the making of geography in the Aufklärung.